Pathos and Its Implication in the Philokalia Fathers - Hendi, Hendi; Jihole, Deswita (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2021)
This article is a review of πάθος (pathos; lust; desire) according to the Philokalia fathers. Pathos is the irrational expression of the soul. It arises from human decisions and choices (free will) alienated from Christ and becomes the disease of the soul (heart). This paper examines pathos, a list of pathos, the pathos process, and how to heal the pathos. The method of the study is the literature review by analyzing the Philokalia texts and other resources. Philokalia is a set of spiritual writings of the Church Fathers based on the Orthodox spiritual tradition. Pathos can only be healed by spiritual practice or discipline (ascesis). Each pathos requires a different ascesis. Jesus Prayer, nepsis, and prayer of the heart are the primary therapies for the sickness of the soul (pathos). The therapy is the purification of the soul to achieve theosis (becoming the likeness of Christ).